Literacycloud : Alternatif Media Pembelajaran Dalam Meningkatkan Kemampuan Membaca Siswa Sekolah Dasar Kelas Rendah - Anastasya Benedicta S; Aulia Fitrianti; Clariza Apriliana; Yohana Apriani (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2021)
Education as the foundation of civilization has an important role in the advancement of science. In addition, education also has a large part in national development and the formation of the character of the nation that is an indicator of the progress of a nation. Education is a teaching and learning process that involves teachers and students. Interaction between teachers and students is called learning where teachers transfer their knowledge to students to stimulate the curiosity of students in understanding the material taught. Learning itself will not work well without the medium of learning. More precisely, the learning media becomes a lighter for the interaction of teaching staff with students so as to create connectivity in the teaching and learning process. There are two learning media, one of which is online learning media. Online learning media is a digital learning media. This literature research discusses the online learning media Literacycloud as an alternative to learning media in improving the reading skills of low-grade elementary school students.